2014
DOI: 10.1158/1078-0432.ccr-13-1330
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Epithelial-to-Mesenchymal Transition with Met Inhibitors Reverts Chemoresistance in Small Cell Lung Cancer

Abstract: Purpose: Met receptor phosphorylation is associated with poor prognosis in human small cell lung cancer (SCLC). The aim of our work was to investigate the effects of hepatocyte growth factor (HGF)/ Met-mediated epithelial-to-mesenchymal transition (EMT) in SCLC and to evaluate the role of Met inhibition in mesenchymal/chemorefractory SCLC models.Experimental Design: SCLC models of HGF-induced EMT were evaluated in vitro and in vivo (subcutaneous xenografts in BALB/c nude mice) for chemosensitivity and response… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 34 publications
1
100
1
Order By: Relevance
“…MET is normally expressed by cells of epithelial origin, while expression of HGF is restricted to cells of mesenchymal origin (70). HGF mediated EMT induces resistance to chemotherapy in SCLC (71), but so far no reports on MET induced EMT and resistance to EGFR-TKIs in NSCLC exist. Upon HGF stimulation, MET induces several biological responses related to invasive cell growth and abnormal MET activation in cancer correlates with poor prognosis.…”
Section: Metmentioning
confidence: 99%
“…MET is normally expressed by cells of epithelial origin, while expression of HGF is restricted to cells of mesenchymal origin (70). HGF mediated EMT induces resistance to chemotherapy in SCLC (71), but so far no reports on MET induced EMT and resistance to EGFR-TKIs in NSCLC exist. Upon HGF stimulation, MET induces several biological responses related to invasive cell growth and abnormal MET activation in cancer correlates with poor prognosis.…”
Section: Metmentioning
confidence: 99%
“…Firstly, tumor-infiltrating neutrophils (TINs), the most important 'fertilizers' in the 'soil' (8,15), lose their conventional antitumor characteristics and acquire a pro-tumor phenotype in the presence of transforming growth factor-β (TGF-β) (44). In our previous study, TIN count was revealed to serve as a prognostic factor and to promote epithelial-mesenchymal transition (EMT) in esophageal cancer (45), which may be a key process involved in regulating chemoresistance in malignant tumors (46)(47)(48). However, TIN is not a conventional indicator for detection due to difficulty in its measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, slower-growing nonneuroendocrine SCLC cells in tumors, such as Notchactive SCLC cells may be inherently more resistant to chemotherapeutics as shown in a GEMM (discussed above) (52) and may help the neuroendocrine cells survive chemotherapy. SCLC cells with a mesenchymal phenotype may also be intrinsically more chemoresistant (68,69). Furthermore, interactions of SCLC cells with their microenvironment, including the extracellular matrix, may promote chemoresistance, although this has not been tested in animal models (70)(71)(72)(73)(74).…”
Section: Chemoresistant Sclcmentioning
confidence: 99%